2019
DOI: 10.1108/rsr-06-2019-0041
|View full text |Cite
|
Sign up to set email alerts
|

Developing and assessing a graduate student reference service

Abstract: Purpose The purpose of this paper is to formally assess the training program received by information studies graduate students and the reference services they provided at a research-intensive university. Design/methodology/approach A qualitative content analysis was used to evaluate if graduate students incorporated the training they received in their provision of reference services. The students’ virtual reference transcripts were coded to identify the level of questions asked, if a reference interview occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…These traits are not necessarily limited to professional librarians. Fundamental to student assistants performing reference services at a high level is their understanding of the quality standard, a commitment to said standard and their completion of training necessary to perform at that designated level (Barrett and Greenberg, 2018;Bennett and Stout, 2021;Canuel et al, 2019;Faix, 2014;Harrington et al, 2021;Langan, 2012;Tang, 2020;Stanfield and Palmer, 2010). A review of training programs for student assistants who work closely with library users will illustrate the keys to success in training students for reference duties.…”
Section: Quality Of Student Assistants' Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These traits are not necessarily limited to professional librarians. Fundamental to student assistants performing reference services at a high level is their understanding of the quality standard, a commitment to said standard and their completion of training necessary to perform at that designated level (Barrett and Greenberg, 2018;Bennett and Stout, 2021;Canuel et al, 2019;Faix, 2014;Harrington et al, 2021;Langan, 2012;Tang, 2020;Stanfield and Palmer, 2010). A review of training programs for student assistants who work closely with library users will illustrate the keys to success in training students for reference duties.…”
Section: Quality Of Student Assistants' Workmentioning
confidence: 99%
“…Analysis of chat transcripts at the Humanities and Social Sciences Library at McGill University in Montreal, Canada, demonstrated that most interactions involve basic questions, or known item searches (Canuel et al, 2019). Answering directional questions ("where is the bathroom?"…”
Section: Reference Trainingmentioning
confidence: 99%
“…Training documentation is particularly important as new hires typically do not join the library at the same time and one-on-one training for chat operators requires a greater time commitment from already busy librarians than does a group training session (Farrell and Leousis, 2017;Mavodza, 2019). A training program for graduate student library assistants at McGill University, Canada, for example, consisted of methods of conducting a proper reference interview, orienting students to the library, making users aware of different catalogs, databases and library resources, training on the features of the chat platform, and 30 h of time spent shadowing experienced librarians while they provided reference services (Canuel et al, 2019). Chat transcripts can also help guide training for chat operators by providing ready-tohand examples of what does and does not work well from real-life examples (VanScoy and Oakleaf, 2007;Jacoby et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, do librarians, library staff and students all provide equal levels of service? Realistically, many academic libraries have discovered that there is not enough time for librarians to serve in chat for extended hours per day, given their regular duties, so students can be brought up to "good enough" with proper training and librarian supervision (Lux and Rich, 2016;Canuel et al, 2019;Cabaniss, 2015;Farrell and Leousis, 2017;Barrett and Greenberg, 2018). Staffing chat to meet user needs can be determined relative to the student population and observed service usage patterns (Barrett and Greenberg, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…5 In particular, small and medium-sized academic libraries have seen a shortage of librarians and need to hire and train student employees, so librarians' capabilities for real-time quick and easy analysis and assessment will become critical in helping them take appropriate actions to best meet user needs. 6 As part of an effort to develop a quick and easy analysis tool for large volumes of chat transcripts, this study applied topic modeling, which is a statistical technique "for learning the latent structure in document collections" or "a type of statistical model for finding hidden topical patterns of words." 7 We compared outcomes of different types of topic modeling techniques and attempted to propose topic modeling techniques that would be most appropriate in the context of chat reference transcript data.…”
Section: Introductionmentioning
confidence: 99%